Funding and Defunding Military Spending - 200 Years of Evidence - Armin A. Bolouri; Tim Lohse; Salmai Qari (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We provide the first global, long-run analysis of how governments fund and de-fund military spending. Constructing a panel of 167 countries from 1817 to 2024, we estimate fiscal responses to armaments and disarmaments, including wartime shifts. Deficit spending is the primary financing policy, while larger armaments trigger deeper cuts to civilian spending. Fiscal space is a critical moderator: low-debt countries rely mainly on borrowing, whereas high-debt countries resort to taxation and budget reallocations. Armaments and disarma-ments have asymmetric effects: disarmaments only partially reverse prior poli-cies, sustaining elevated civilian spending as a fiscal peace dividend and leaving the state permanently larger.
Keywords: N4; H1; H56; H60; E6; 330; military spending; war Finance; fiscal space; peace dividend